HRRD: a manually-curated database about the regulatory relationship between HPV and host RNA - Yan, Bingqing (Sci Rep, 2020)
HPV (Human papilloma virus) is a kind of small double-stranded DNA viruses which is extremely associated with different cancers. The roles HPV plays in the host were gradually identified through the interaction between it (including its early genes) and host RNA. In recent years, increasing numbers of studies in HPV-related cancers have been published showing the relationship between HPV and host RNA. Here, we present a database named HRRD, which contains the regulatory relationship between HPV and RNA (mRNA, miRNA and lncRNA). The information was extracted from 10,761 papers in PubMed (up to December 1st, 2019). In addition, the sequence map of HPV (198 genotypes) is also contained. HRRD was designed as a user-friendly web-based interface for data retrieval. It integrated the information of interaction between HPV and RNA, which reflects the relationship between HPV and host. We hope HRRD will further provide a comprehensive understanding of HPV in carcinogenesis and prognosis. HRRD is freely accessible at www.hmuhrrd.com/HRRD.